FOLK ARTS OF BARELA TRIBE: बारेला जनजाति की लोक कलाएँ - Singh Patel, Anand (International Journal of Research -GRANTHAALAYAH, 2019)
Tribal traditional arts are associated with some rituals and festivals. The arts prevalent in the folk, which involve deep process and growth of rituals, are folk arts that should be made as demonstrators. The display has full potential. They should try to give a demonstrative look. आदिवासी पारम्परिक कलाएँ किसी न किसी अनुष्ठान और पर्व.उत्सव से जुड़ी रहती है।लोक में प्रचलित कलाएँ जिनमें अनुष्ठान की गहरी प्रक्रिया और वृद्धि निहित होती है ऐसी लोक कलाएँ जो प्रदर्शनकारी के रूप में बनायी जानी चाहिए।ऐसी विधाएँ जिनमें अनुष्ठान बहुत कम हैं जिनमें प्रदर्शन की पूरी क्षमता है। उन्हें ही प्रदर्शनकारी रूप देने का प्रयास करना चाहिए।